Fresno County Bar Association Luncheon with Boalt Hall Dean Jesse Choper at Smuggler's Inn - Watkins, Howard::::::::: (1989)
San Joaquin College of Law Dean Janice Pearson, Dean Jesse Choper, Judge Jim Paige and Leo Kolligian